2011
DOI: 10.4081/cp.2011.e132
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Bleeding: Audit of a Single Center Experience in Western India

Abstract: Upper gastrointestinal (GI) bleeding is defined as bleeding proximal to the ligament of Treitz. The most important aspect of management of GI bleeding is to locate the site and cause of bleeding. The aim of the study is to find out the common etiology, presentation and management, including the role of upper GI endoscopy. Recent advances have meant that endoscopic hemostatic methods are now associated with a reduced rate of re-bleeding, cost, blood transfusion, length of hospital stay and mortality. A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
7
1
Order By: Relevance
“…Based on the clinical presentation, a greater number of our patients presented with hematemesis only (43.8%). Hematemesis was the most common presentation in studies from 48% 12 to 100% 17 , which was consistent with our findings. Both hematemesis and melena were present in 71.7% 8 and 51% 16 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the clinical presentation, a greater number of our patients presented with hematemesis only (43.8%). Hematemesis was the most common presentation in studies from 48% 12 to 100% 17 , which was consistent with our findings. Both hematemesis and melena were present in 71.7% 8 and 51% 16 .…”
Section: Resultssupporting
confidence: 92%
“…In our study, 19(15.7%) presented with shock (systolic blood pressure SBP<90 mmHg). Similar findings of patients presenting with shock were seen in 21.7% 8 , 14% 12 , 36.7% 17 of UGIBD. Mean arterial blood pressure was low (73.71±10.95) 12 and hypotension was noted in 14.8% 18 of patients at presentation.…”
Section: Resultssupporting
confidence: 80%
“…The mean age in this study was found to be 52.78 ± 13.52 years. Rathod JB et al 13 in 2011 reported haematemesis as most common presenting symptom same comparable as with our study. However, a bleeding duodenal ulcer is likely to be presented with melaena more frequently than haematemesis while a bleeding gastric ulcer patient may present with haematemesis more frequently than melaena.…”
Section: Discussionsupporting
confidence: 92%
“…A study 6 from Rajshahi also reported that most of the patients with upper gastrointestinal haemorrhage presented with both haematemesis and melaena (42%). Rathod JB et al 13 in 2011 reported haematemesis as most common presenting symptom. In a study 2 from Sikkim, India the commonest presentation was haematemesis and melaena in over half of the patients like other studies, 4,14 which predict massive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 But western studies report a higher age at presentation, 9,10,11 which is due to elderly population in their community. Eighty percentage of the study population presented with haematemesis, 27.2% had massive haematemesis, and 39.4% presented with shock but unlike other studies 12 pain abdomen was present only in 13% that is due to higher number of patients with variceal bleed in our study. In our study population, 67 patients had co-morbidities with diabetes (55.2%) being the commonest co-morbidity.…”
Section: Discussioncontrasting
confidence: 69%